A chromosome-scale genome assembly of turmeric provides insights into curcumin biosynthesis and tuber formation mechanism - Yin, Yanpeng; Xie, Xiaofang; Zhou, Luojing; Yin, Xianmei; Guo, Shuai; Zhou, Xianjian; Li, Qingmiao; Shi, Xiaodong; Peng, Cheng; Gao, Jihai (Frontiers in Plant Science, 2022)
Curcuma longa, known as the ‘golden spice’ and ‘life spice’, is one of the most commonly utilized spices in the world and also has medicinal, cosmetic, dye and flavoring values. Herein, we present the chromosomal-level genome for turmeric to explore the differences between tubers and rhizomes in the regulation of curcumin biosynthesis and the mechanism of tuber formation. We assembled the turmeric genome into 21 pseudochromosomes using Pacbio long reads complemented with Hi-C technologies, which has a total length of 1.11 Gb with scaffold N50 of 50.12 Mb and contains 49,612 protein‑coding genes. Genomic evolutionary analysis indicated that turmeric and ginger have shared a recent WGD event. Contraction analysis of gene families showed possible roles for transcription factors, phytohormone signaling, and plant-pathogen interactions associated genes in adaptation to harsh environments. Transcriptomic data from tubers at different developmental stages indicated that candidate genes related to phytohormone signaling and carbohydrate metabolic responses may be associated with the induction of tuber formation. The difference in curcumin content between rhizomes and tubers reflected the remodeling of secondary metabolites under environmental stress, which was associated with plant defense in response to abiotic stresses. Overall, the availability of the C. longa genome provides insight into tuber formation and curcumin biosynthesis in turmeric as well as facilitating the understanding of other Curcuma species.